STUDI KEPUASAN PESERTA TERHADAP PENYELENGGARAAN HONDA BIKERS DAY 2025: FAKTOR FASILITAS, AKTIVITAS DAN KEBERSAMAAN - Hendriady de Keizer; Riffka Fauzany; Rakhmat Haryono; Gunardi Gunardi (PUBLISHER ABISATYA DINAMIKA ISWARA PUBLISHING, 2026)
This study aims to analyze participants’ satisfaction with the organization of Honda Bikers Day 2025, focusing on three main factors: facilities, activities, and togetherness. The event is part of a community engagement strategy organized by PT Astra Honda Motor to strengthen loyalty and solidarity among Honda bikers in Indonesia. This research employed a descriptive qualitative approach supported by simple quantitative data collected through questionnaires distributed to 93 participants. Data analysis was conducted descriptively using frequency distribution and thematic analysis of open-ended responses. The findings indicate that overall participant satisfaction falls within the fairly satisfied to satisfied category. The activity and togetherness factors were the most influential in shaping satisfaction, particularly through touring activities, music performances, and inter-community interactions that enhanced solidarity. However, the facilities aspect still requires improvement, especially regarding toilet cleanliness, rest areas, and venue management. It can be concluded that the success of Honda Bikers Day 2025 is more strongly influenced by the value of togetherness and social experience than by technical facility aspects alone. Keywords: participant satisfaction, community event, facilities, activities, togetherness, Honda Bikers Day